39 Child and adolescent injuries in the Arab Gulf: understanding the burden and risk factors. (1st September 2016) - Hyder, Adnan A; Mehmood, Amber; Peralta, Ruben; Consunji, Rafael; Allen, Kate
Abstract : Background: The WHO estimates that every day 2, 000 children and adolescents are killed by preventable injuries. In the high-income Arab Gulf States, the under-5 injury mortality rate is 22.2 per 100, 000, which is higher than any other high-income region in the world. Limited research is available on the burden and risk factors associated with child and adolescent injuries in this area of the world. This panel session aims to address this knowledge gap by sharing results from child-injury studies conducted in three high-income developing countries in the Arab Gulf. Moderator: Dr. Adnan A Hyder, Johns Hopkins International Injury Research Unit (JH-IIRU, USA) Talk 1: Pattern of childhood injuries: Findings from hospital based injury surveillance system in Oman - Dr. Amber Mehmood, Johns Hopkins International Injury Research Unit, USA Abstract: Findings from a trauma registry implemented in two hospitals in the Sultanate of Oman. Results from the registry were used to characterise the burden of injuries among children and adolescents (<18 years). Recommended areas for action will be discussed. Talk 2: Designing a successful intervention program to increase child restraint use in Qatar - Dr. Ruben Peralta/Dr. Rafael Consunji, Hamad Medical Corporation, Qatar Abstract: Considerations and lessons-learned from the development and roll-out of an intensive tutorial to increase child restrain use among parents in Doha, Qatar will be presented along with 5-year time-trends for child road traffic injury rates. Using a burden of disease approach to quantify injuries among youth in the United Arab Emirates – Dr. Kate Allen, Johns Hopkins International Injury Research Unit, USA Abstract: A burden of disease analysis was conducted in the UAE using 2010 data from the Ministry of Health. Age, sex and nationality-specific rates of Years of Life Lost were calculated and used to identify priority areas for child injury prevention in the UAE. Discussion will focus on how such an analytical approach can be used to better understand the burden of injuries. Discussant: Dr. Olakunle Alonge, Johns Hopkins International Injury Research Unit, USA Q&A - Dr. Adnan A Hyder, Johns Hopkins International Injury Research Unit, USA